The Gag polypeptides of the Drosophila 1731 retrotransposon are associated to virus-like particles and to nuclei. - Haoudi, A.; Kim, M.H.; Champion, S.; Best-Belpomme, M.; Maisonhaute, C. (FEBS Letters, 1995)
1731 is a Drosophila melanogaster retrotransposon whose nucleotide sequence shows a proviral architecture with two long terminal repeats (LTRs) framing two internal Open Reading Frames (ORFs). The pol ORF2 of this mobile genetic element was demonstrated to code for an active Reverse Transcriptase (RT) and the ORF1 is expected to code for the structural Gag proteins of the virus-like particles (VLP). Using specific anti-Gag antibodies, we have characterized the 1731 Gag polypeptides expressed either in vitro or in Kc Drosophila melanogaster cultured cells. Together with the 1731 RT, the largest, likely post-translationaly-modified Gag polypeptides are gathered into cytoplasmic virus-like particles. Moreover and consistent with the nuclear localization signal present in the Gag sequence, we observed that a short 1731 Gag polypeptide is associated to the cell nuclei.